A new code-based encryption scheme and its applications. (2017) - Tang, Jiayong; Zhang, Fangguo
More and more data has to be dealt with in the current network computing. An extremely efficient encryption algorithm can greatly improve the efficiency and security of the process in large data environment. As a significant candidate of post-quantum cryptosystem, McEliece public-key cryptosystem (PKC) has one remarkable advantage that it has a very fast and efficient encryption process. In this paper, we put forward a new efficient CPA-secure variant of the McEliece cryptosystem whose advantage is that we can enlarge the plain-text space while the cipher-text space unchanged. We formally prove the security of the scheme. Our proof is based on the learning parity with noise (LPN) problem. We also extend our scheme to a CCA-secure cryptosystem and a signcryption.